2013
DOI: 10.1109/tdei.2013.6508755
|View full text |Cite
|
Sign up to set email alerts
|

A modified Maxwell model for characterization of relaxation processes within insulation system having non-uniform aging due to temperature gradient

Abstract: Modeling of dielectric relaxation function φ(t) by a distribution of exponential decay functions is advantageous due to its monotonically decreasing property which ensures that φ(t) is integrable over any period of time. Several equivalent circuits based on simple combination of energy storing and dissipating elements are available in literature which are capable of modeling φ(t). One of the widely used two-parameter equivalent circuit for dielectric response modeling of various polymeric dielectric as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 17 publications
0
61
0
Order By: Relevance
“…Therefore, it can be understood that a single RC branch has limited capability to fully describe the behavior of a dipole groups distributed throughout the insulation [7]. Though the effect of measurement temperature has been analyzed to a significant extent by CIGRE TF.D1.0109 [4] and other researchers [8], few literature are available that address the effect of non-linear aging and its subsequent effect on insulation model parameters. The authors have shown that the Modified Debye Model shown in Figure 6 is capable of modeling this non-linear aging [7] and hence provides a better representation of the insulation.…”
Section: Non-uniform Aging In Transformer Insulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it can be understood that a single RC branch has limited capability to fully describe the behavior of a dipole groups distributed throughout the insulation [7]. Though the effect of measurement temperature has been analyzed to a significant extent by CIGRE TF.D1.0109 [4] and other researchers [8], few literature are available that address the effect of non-linear aging and its subsequent effect on insulation model parameters. The authors have shown that the Modified Debye Model shown in Figure 6 is capable of modeling this non-linear aging [7] and hence provides a better representation of the insulation.…”
Section: Non-uniform Aging In Transformer Insulationmentioning
confidence: 99%
“…It is reported in [8][9] that with the passage of time, cellulosic parts of transformer insulation undergoes nonuniform aging. It is further reported in [8] that unlike Modified Debye Model (MDM), CDM is incapable of modeling the effect of such non-uniform aging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the insulation shown in Figure 2 is approximated by Figure 3, the insulation model (shown in Figure 1) can be represented in the form shown in Figure 4. It is shown in [8] that unlike CDM, the Modified Debye Model (MDM) shown in Figure 4 is capable of taking into account the effect of the non-uniform aging in cellulosic parts and hence is a better representation of the overall insulation. It should be mentioned here that effect of non-uniform aging on dielectric response is difficult to study using scaled down physical model due to reduced volume of cellulosic material and lower power rating.…”
Section: Basic Theory Behind Formulation Of Modified Debye Modelmentioning
confidence: 99%
“…Though the effect of measurement temperature on dielectric response of insulation has been analyzed to a significant level by CIGRE TF.D1.0109 [1] and other researchers [7], only few papers are available that analyzes the effect of non-uniform aging on dielectric response and hence on insulation model parameters. It is shown in [8] that Modified Debye Model, a modification of CDM, is capable of modeling the non-linear aging of cellulosic parts in insulation.…”
Section: Introductionmentioning
confidence: 99%